Flexural behaviour of two ribbed SFRC slab reinforced with GFRP bars / Adnie Baharin, Hazrina Ahmad, Muhammad Haziq Hizdrami and Mohd Hisbany Mohd Hashim - Baharin, Adnie; Ahmad, Hazrina; Hizdrami, Muhammad Haziq; Mohd Hashim, Mohd Hisbany (2023)
This study presents the results of an experimental investigation on the application of steel fibres (SF) in combination with glass fibre reinforced polymer (GFRP) bars as the steel reinforcement replacement in a ribbed slab structure. The promising ability of steel fibre reinforced concrete (SFRC) to reduce the formation of cracks and increase the tensile strength of concrete has made it an attractive composite material for numerous civil construction applications. However, previous research had shown that the performance of the steel fibres on their own to replace steel reinforcements is still in doubt. Therefore, the GFRP bar is chosen due to its structural performance with flexural reinforcement with less weight and corrosion resistance. The influence of the steel fibres and GFRP bars on the two-ribbed slab flexural performance was investigated. Three (3) numbers of slab panels were cast, consisting of one solid SFRC slab (solid-SF), one SFRC ribbed slab (rib-SF), and one SFRC ribbed slab reinforced with GFRP bars (rib-SF-GFRP). All slab samples measuring 1000 mm x 1500 mm x 75 mm thickness were tested under bending and the results showed that the SFRC ribbed slab reinforced with GFRP.